2021
DOI: 10.3390/genes12111724
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Shedding Fruit Elaeis oleifera Palm Reveals Perturbations to Hormone Signaling, ROS Homeostasis, and Hemicellulose Metabolism

Abstract: The developmentally programmed loss of a plant organ is called abscission. This process is characterized by the ultimate separation of adjacent cells in the abscission zone (AZ). The discovery of an American oil palm (Elaeis oleifera) variant that does not shed its has allowed for the study of the mechanisms of ripe fruit abscission in this species. A comparative transcriptome analysis was performed to compare the fruit AZs of the non-shedding E. oleifera variant to an individual of the same progeny that sheds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Another study determined that SlPIN1-regulated auxin efflux influences the flower abscission process [ 14 ]. To date, several studies on blue honeysuckle, tomato flowers, and fruit trees revealed that considerable changes to plant hormone contents promote the abscission of fruit organs [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study determined that SlPIN1-regulated auxin efflux influences the flower abscission process [ 14 ]. To date, several studies on blue honeysuckle, tomato flowers, and fruit trees revealed that considerable changes to plant hormone contents promote the abscission of fruit organs [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%